2022
DOI: 10.1371/journal.pone.0263015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of problem-based learning modules within blended learning courses in medical statistics – A randomized controlled pilot study

Abstract: Problem-based learning (PBL) allows students to learn medical statistics through problem solving experience. The aim of this study was to assess the efficiency of PBL modules implemented in the blended learning courses in medical statistics through knowledge outcomes and student satisfaction. The pilot study was designed as a randomized controlled trial that included 53 medical students who had completed all course activities. The students were randomized in two groups: the group with access to PBL modules wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Twenty‐two RCTs involving 1969 participants were included (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Dyke et al, 2001; Faisal et al, 2016; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim, 2019; Kim & Shin, 2014, 2016; Lee & Son, 2022; Li et al, 2020; Lian & He, 2013; Lin et al, 2010; Lohse et al, 2003; Peng et al, 2021; Pourshanazari et al, 2013; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019). The numbers of participants in the experimental and control groups were 1003 and 966, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐two RCTs involving 1969 participants were included (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Dyke et al, 2001; Faisal et al, 2016; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim, 2019; Kim & Shin, 2014, 2016; Lee & Son, 2022; Li et al, 2020; Lian & He, 2013; Lin et al, 2010; Lohse et al, 2003; Peng et al, 2021; Pourshanazari et al, 2013; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019). The numbers of participants in the experimental and control groups were 1003 and 966, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the performance outcomes were objective assessments from tutors or supervisors. Fifteen studies reported analyzable outcomes of performance for the meta‐analysis (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim & Shin, 2014; Lee & Son, 2022; Li et al, 2020; Lin et al, 2010; Peng et al, 2021; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019), among which all 15 reported post‐interventional performance scores, and seven also reported performance scores before interventions (Jamshidi et al, 2021; Khatiban et al, 2019; Kim & Shin, 2014; Lee & Son, 2022; Lin et al, 2010; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Table 2). The maximum score ranged from 3 to 100.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Banyak permasalahan dalam pembelajaran metode statistika dapat diselesaikan menggunakan modul pembelajaran (Andersson & Logofatu, 2017). Penggunaan modul menjadikan pembelajaran lebih menyenangkan, mendorong keaktifan proses belajar, dan memberian kesempatan untuk membuat koneksi pada materi lain maupun situasi kehidupan sehari-hari (Bukumiric et al, 2022).…”
unclassified